Excess phosphorus from compost applications in urban gardens creates potential pollution hotspots. (13th September 2019) - Small, Gaston; Shrestha, Paliza; Metson, Geneviève Suzanne; Polsky, Katherine; Jimenez, Ivan; Kay, Adam
Abstract: Urban sustainability initiatives often encompass such goals as increasing local food production, closing nutrient loops through recycling organic waste, and reducing water pollution. However, there are potential tradeoffs among these desired outcomes that may constrain progress. For example, expansion of urban agriculture for food production may create hotspots of nutrient pollution if nutrient recycling is inefficient. We used gardener and urban farmer survey data from the Twin Cities Metropolitan Area (Minnesota, USA) to characterize phosphorus (P) and nitrogen (N) inputs and harvest in order to determine nutrient use efficiencies, and measured soil P concentrations at a subset of these sites to test whether excess soil P was common. All survey respondents (n = 142) reported using some form of soil amendment, with plant-based composts being the most common. Median application rates were 300 kg P/ha and 1400 kg N/ha. Median nutrient use efficiencies were low (2.5% for P, 5.0% for N) and there was only a weak positive relationship between P and N inputs and P and N harvested in crop biomass. Garden soils had a median Bray P value of 80 ppm, showing a buildup of plant-available P far exceeding recommended levels. Our results show that urban gardens are characterized by high nutrient inputs and inefficient conversion of these nutrients into crops, leading to buildup and potential loss of P and N from garden soils. Although urban gardens make up only 0.1% of land area in the Twin Cities, compost application to these urban gardens still constitutes one of the largest inputs of P to the watershed. In order to maximize desired outcomes from the expansion of urban agriculture (UA), it will be necessary to target soil amendments based on soil nutrient levels and crop nutrient demand.